IMPLIKASI LEMBAGA SOSIAL DALAM PENINGKATAN KESEJAHTERAAN YATIM DAN DHUAFA DITINJAU DARI HUKUM EKONOMI SYARIAH(Studi Kasus di Lembaga Mutiara Qolbu Indonesia, Jakarta Timur) - Sabililah, Sabi; Rohmah, Siti Ngainnur (Journal of Islamic Studies, 2023)
The poverty rate is still relatively high, there are social and economic inequalities in society, and economic conditions are not evenly distributed, causing various social services in the form of institutions to be present in the community, the position of social institutions is very important to protect orphans and dhuafa, so this is a form of implementation. a science of welfare. The purpose of this research is to explain the implications of social institutions for increasing the welfare of orphans and the poor in order to determine the increase in their welfare in the Mutiara Qolbu Indonesia Social Institution in terms of Sharia Economic Law. This study uses a qualitative research method using an empirical juridical approach or legal sociology. Data collection techniques consist of observation, interviews and documentation. The results of the study show that the implications of social institutions for improving the welfare of orphans and dhuafa at the Mutiara Qolbu Indonesia Social Institute, East Jakarta, have a positive impact on the welfare of orphans and dhuafa, which can be seen in the quality of life in terms of material, physical, mental and spiritual. Increasing the welfare of orphans and poor people at the Mutiara Qolbu Indonesia Institute, is in accordance with the review of sharia economic law. This can be seen from the fulfillment of economic welfare, the fulfillment of the basic needs of orphans and the poor, the optimal use of power, the distribution of wealth, wealth, income and development results in a fair and comprehensive manner, guaranteeing individual freedom, equal rights and opportunities, mutual assistance and justice.